2022
DOI: 10.3389/fgene.2022.825652
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Analysis of Aedes aegypti Mosquitoes From Sudan Revealed Recent Independent Colonization Events by the Two Subspecies

Abstract: Increases in arbovirus outbreaks in Sudan are vectored by Aedes aegypti, raising the medical importance of this mosquito. We genotyped 12 microsatellite loci in four populations of Ae. aegypti from Sudan, two from the East and two from the West, and analyzed them together with a previously published database of 31 worldwide populations to infer population structure and investigate the demographic history of this species in Sudan. Our results revealed the presence of two genetically distinct subspecies of Ae. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 99 publications
(159 reference statements)
3
10
2
Order By: Relevance
“…The STRUCTURE and ABC analyses indicated genetic admixture between the two genetic groupings originating from Africa or the global population in the intervening geographic regions of Sahil and the Jazan region. The mixing of these two distinct genetic forms of A. aegypti has also recently been inferred to have occurred in Sudan (Elnour et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The STRUCTURE and ABC analyses indicated genetic admixture between the two genetic groupings originating from Africa or the global population in the intervening geographic regions of Sahil and the Jazan region. The mixing of these two distinct genetic forms of A. aegypti has also recently been inferred to have occurred in Sudan (Elnour et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…To investigate the evolutionary history and test the hypothesis of genetic admixture within Saudi Arabia of the ancestral African and pantropical global forms, population samples from Thailand and Uganda were also included to represent these potential source populations (Table 1). Use of a single population to represent each form is reasonable given that there is far greater genetic differentiation between the forms than there is between populations within the forms (Elnour et al., 2022; Gloria‐Soria et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…However, the ease with which the forms are separable here is rare and not in any way typical of Africa. The complexity is increased by the reintroductions of Aaa in the African continent [ 206 ] and by the presence of domestic populations in West Africa [ 4 , 5 ]. The real picture is one of complexity and variation, as many of the useful morphological characters are rarely exclusive to one form and differentiation or determining “which form is present or predominant” at any particular study site, is far from straightforward.…”
Section: Resultsmentioning
confidence: 99%
“…In Sudan, Abuelmaali et al (2021) and Elnour et al (2022) both reported geographically separated populations of a. formosus (in the west) and a. aegypti (in the east). Elnour et al (2022) wrote that "Analysis supports a scenario in which Ae. aegypti entered Sudan on at least two independent occasions nearly 70-80 years ago."…”
Section: Aedes (Stegomyia) Aegypti (Linnaeus)mentioning
confidence: 98%